Greater rate of weight loss predicts paediatric hospital admission in adolescent typical and atypical anorexia nervosa - Brennan, Cliona; Cini, Erica; Illingworth, Sarah; Chapman, Simon; Simic, Mima; Nicholls, Dasha; Chapman, Victoria; Simms, Conor; Hayes, Ellen; Fuller, Sarah; Orpwood, Jade; Tweedy, Nichola; et al. (Springer Nature, 2024)
Hospital admissions for eating disorders (ED) are rapidly increasing. Limited research exists evidencing the factors that lead to hospital admissions or their outcomes. The current study aimed to identify predictors of hospital admission in adolescents with anorexia nervosa (AN) or atypical anorexia nervosa (AAN). Prospective observational study including participants (n = 205) aged 11–18 and diagnosed with AN or AAN at initial ED assessment, across eight London clinics. Physical health parameters at assessment, including heart rate, blood pressure, temperature and rate of weight loss, were compared between adolescents who were admitted to a paediatric ward following assessment and those who were not admitted. The mean rate of weight loss prior to assessment was significantly higher, and mean energy intake significantly lower, in the admitted vs not admitted groups (1.2 vs 0.6kg/week, p < 0.001 and 565 kcal/day vs 857 kcal/day, p < 0.001), independent of degree of underweight. No significant differences were identified between groups in all other parameters of physical risk. Underweight adolescents with AN were equally likely to be admitted as non-underweight adolescents with AAN. Conclusion: This study provides evidence on predictors of hospital admission, from a sample representing the London area. The assessment of weight loss speed, duration and magnitude are recommended as priority parameters that inform the risk of deterioration and the likelihood of hospital admission in adolescent AN and AAN. Further research investigating outcomes of these hospital admission is needed. What is Known: • Hospital admissions for eating disorders (ED) are rapidly increasing. • Limited research exists evidencing the factors that lead to hospital admissions, or their outcomes. What is New: • This study provides evidence on predictors of hospital admission in young people with typical and atypical anorexia nervosa. • Weight loss speed, duration, and magnitude are recommended as priority parameters that inform the risk of deterioration and the likelihood of hospital admission in this patient group.